Childhood vaccinations and adult schooling attainment: Long-term evidence from India's Universal Immunization Programme. (April 2020) - Nandi, Arindam; Kumar, Santosh; Shet, Anita; Bloom, David E.; Laxminarayan, Ramanan
Abstract: Routine childhood vaccines are among the most cost-effective life-saving interventions. In addition, vaccines have been linked with reduced stunting and improved health and other outcomes in later life. However, evidence on such long-term benefits remain inadequate. In this study, we examined the associations between the initiation and implementation of the Universal Immunization Programme (UIP) in India and schooling attainment among adults. We obtained district-level data on the rollout of the UIP in 1985–1990 and matched those with data from the National Family Health Survey of India, 2015–2016. Adults who were born in the five years before and after the rollout period (1980–1995) and always lived in the same location were included in the analysis (n=109, 908). We employed household, village or city ward, district, and state fixed-effects linear regression models, which incorporated a wide range of socioeconomic and demographic indicators and community-level infrastructure, amenities, and access to healthcare. We compared schooling attainment in years among individuals who were born during or after the UIP was implemented in their districts (intervention group) with those who were born before UIP implementation (control group). In household fixed-effects analysis, intervention group adults attained 0.18 (95% confidence interval [CI]: 0.02, 0.33; p<0.05) more schooling grades as compared with control group adults from the same household. In village or city ward, district, and state fixed-effects analysis, intervention group adults attained 0.23 (95% CI: 0.13, 0.32; p<0.001), 0.29 (95% CI: 0.19, 0.38; p<0.001), and 0.25 (95% CI: 0.1, 0.39; p<0.01) additional schooling grades, respectively, compared to the control group. In subgroup analyses, positive associations between UIP implementation and schooling grades were observed among women and among rural, urban, and richer households. Our results support the association of vaccines with improved school attainment. Highlights: Vaccines could provide a broad range of health and non-health benefits. We examined the link between childhood vaccination and adult schooling in India. India's UIP was associated with 0.2–0.3 additional schooling grades.